2005
DOI: 10.1242/dev.02016
|View full text |Cite
|
Sign up to set email alerts
|

Agrin regulates growth cone turning ofXenopusspinal motoneurons

Abstract: The pivotal role of agrin in inducing postsynaptic specializations at neuromuscular junctions has been well characterized. Increasing evidence suggests that agrin is also involved in neuronal development. In this study,we found that agrin inhibited neurite extension and, more importantly, a gradient of agrin induced repulsive growth-cone turning in cultured Xenopus spinal neurons. Incubation with a neutralizing antibody to agrin or expression of the extracellular domain of muscle-specific kinase, a component o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…Furthermore, this activation seems to be essential for the clustering of acetylcholine receptors in the presence of agrin (Weston et al, 2000). In contrast, agrin decreased Rac 1 activation in cultured hippocampal neurons (Xu et al, 2005). The lack of activation of Rac 1 under our experimental conditions, together with those previous observations, suggested that the ability of agrin to activate this signaling pathway might be cell-type specific.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Furthermore, this activation seems to be essential for the clustering of acetylcholine receptors in the presence of agrin (Weston et al, 2000). In contrast, agrin decreased Rac 1 activation in cultured hippocampal neurons (Xu et al, 2005). The lack of activation of Rac 1 under our experimental conditions, together with those previous observations, suggested that the ability of agrin to activate this signaling pathway might be cell-type specific.…”
Section: Discussionsupporting
confidence: 67%
“…Similar results were obtained when sensory and motor neurons were grown on cells expressing different agrin isoforms (Chang et al, 1997). More recently, it has been shown that agrin also induced repulsive growth cone turning in cultured Xenopus spinal neurons (Xu et al, 2005). In addition to these direct effects, agrin could regulate neurite elongation by modulating the function of neurite-promoting molecules.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…More disturbingly, the two sets of BDNF data (Song et al. , 1997; Stein & Tessier‐Lavigne, 2001) are inconsistent, and an agrin gradient causes repulsion without affecting axonal growth rate, while bath application of agrin reduces growth rates (Xu et al. , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Using the similar growth cone turning assay, Nancy Ip and colleagues [44] at the HUSK and ION discovered that agrin, a molecule previously known to induce postsynaptic specializations at neuromuscular junctions, inhibits the neurite extension in cultured Xenopus spinal neurons. A gradient of agrin induced repulsive growth cone turning in a PI 3 -kinase-and [Ca 2+ ] i -dependent way.…”
Section: Rho Gtpases Signaling In Nerve Growth Cone Guidancementioning
confidence: 99%